Christian family role in implementing Christian education in family context to Christian character building - Kresbinol Labobar (International Journal of Humanities and Innovation (IJHI), 2022)
Christian families are the primary institution in forming children's character into one that reflects Christlikeness. Instructing, educating, and guiding their children to become God-fearing individuals is a crucial responsibility that parents should take very seriously. This makes it necessary for them to take on a variety of roles in their children's character education, including 1) religious teacher, teaching their kids the fundamentals of Christianity to help them develop spiritual intelligence, 2) religious educator, educating kids faith-based applications to help them develop good personalities, and 3) religious role model, influencing their kids' lives. Children's character development leads to four outcomes: 1) a life filled with Christlike qualities that serve as a benchmark for their Christian faith; 2) a life guided by the Holy Spirit, who transforms children's lives; 3) an exemplary Christian life as a result of maturity, and 4) a life that bears the fruit of the Spirit.